D-balanced squeezing function. Issue 4 (3rd April 2023) - Gupta, Naveen; Kumar Pant, Sanjay
Abstract : We introduce the notion of d -balanced squeezing function motivated by the concept of generalized squeezing function given by Rong and Yang. In this work, we study some of its properties and its relation with the Fridman invariant.